The tests to determine 'constructive dismissal': the Malaysian legal perspectives - Md. Dahlan, Nuarrual Hilal; Kamarudin, Abdul Rani (2005)
In so far as Malaysia is concerned, there are certain tests adopted by the courts to determine whether the acts of the employer tantamount to constructive dismissal or not. These tests are, - the 'Contract Test' and the 'Just and Equitable Test or Unreasonable Test'. However, courts in Malaysia have yet to resolve which one of these tests is the most prevailing and practical one? There are cases that apply the former test whilst in others the latter test is applied. This paper attempts to define what are these tests, their origins, rationale and applications in cases involving constructive dismissal and to forward suggestions to improve and suggest the best test in determining 'constructive dismissal' in Malaysia.